Women artists in history: from antiquity to the 20th century - Slatkin, Wendy (Prentice-Hall, 1985)
"The careers and accomplishments of women creators in Western Civilization are described in an accessible and informative mattner in the Second Edition of Women Artists in History: From Antiquity to the 20th Century. Over sixty artists, mostly painters and sculptors, are featured in this book. Selections were based on each woman's unique and important contributions to the history of art. each artist measures up to the same rigorous standards applied to male artists in other survey texts. To understand and appreciate the achievements of these outstanding women, this volume takes a thorough look at the cultural environment in which they lived and worked, as well as the social, economic, and demographic factors that influenced their art." –From back cover
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Feminism and art history: questioning the litany - Broude, Norma; Garrard, Mary D. (Harper & Row, 1982)
A long-needed corrective and alternative view of Western art history, these seventeen essays by respected scholars are arranged chronologically and cover every major period from the ANcient 2gypt to the present. While several of the essays deal with major woman artists, the book is essentially about western art history and the extent to which it has been distorted, in every period, by sexual bias. With 306 illustrations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; Feminism and art; Feminism in art; amérique du nord; amériques; antiquité; arts; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; moyen-âge; occident; premier cycle; périodes historiques; régions géographiques; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques